Dimensionamento de uma usina fotovoltaica em uma borracharia - Monteiro, Douglas Leiba (2023)
Photovoltaic minigeneration is a small-scale electric power generation system using photovoltaic solar panels. In this system, solar energy is converted into electricity through the photovoltaic effect, in which photovoltaic cells in solar panels transform sunlight into electrical current. the grid or operate independently, directly feeding local demand. This offers economic, environmental and energy benefits to users and society as a whole. This study focused on designing a solar energy system, with 75 kWp, classified according to current standards as mini-generation, global irradiation data from software was used for sizing the photovoltaic system. The region analyzed for the implantation of the system presented adequate conditions of solar irradiation. The study described the dimensioning methodology for a distributed minigeneration system, including calculations for power, protections and autotransformer, in addition to the requirements for approval by COPEL. The implementation of the system would generate significant monthly savings, with return on investment in about three years, although it would not be able to fully cover the demand due to the contracted demand of the consumer unit.